A very merry bromance - Adams, Lyssa Kay (Adams, Lyssa Kay. Bromance book club (Series), 2022)
"Country music's golden boy Colton Wheeler felt the most perfect harmony when he was with Gretchen Winthrop. But for her, it was a love him and leave him situation. A year later, Colton is struggling to push his music forward in a new direction. If it weren't about to be the most magical time of year and the support of the Bromance Book Club, he'd be wallowing in self-pity. It's hard for immigration attorney Gretchen not to feel a little Scrooge-ish about the excess of Christmas when her clients are scrambling to afford their rent. So when her estranged, wealthy family reaches out with an offer that will allow her to better serve the community, she's unable to say no. She just needs to convince Colton to be the new face of her family's whiskey brand. No big deal... Colton agrees to consider Gretchen's offer in exchange for three dates before Christmas. With the help of the Bromance Book Club, Colton throws himself into the task of proving to her there's a spark between them. But Gretchen and Colton will both need to overcome the ghosts of Christmas past to build a future together"--